4주간의 b-alanine 섭취가 중학교 축구선수의체력과 혈중 젖산농도에 미치는 영향 - 박영훈; Young Hoon Park; 정원상; Won Sang Jung; 이만균; Man Gyoon Lee (Ch'eyuk kwahak yŏn'gu, 2014)
b-alanine의 섭취는 체내 완충물질인 카르노신(carnosine)의 재합성을 증가시켜 운동 중 발생되는 수소이온(H+)을 중화시킴으로써 피로 지연에 효과가 있는 것으로 보고되었으나, b-alanine의 섭취가 축구선수의 체력에 미치는 영향을 검증한 연구는 매우 미흡한 실정이다. 본 연구는 4주간의 b-alanine 섭취가 중학교축구선수의 신체구성, 유산소성 운동능력, 무산소성 운동능력, 등속성 근기능, 그리고 혈중 젖산농도에 미치는 영향을 규명하는 것이었다. 연구대상자는 S시 소재 S중학교 1~2학년 축구선수 19명으로서, b-alanine 집단(n=10)의 대상자는 1~2주에 일일 2 g, 그리고 3~4주에 일일 3 g의 b-alanine을 섭취하였고, placebo집단(n=9)의 대상자는 동일한 방법으로 옥수수가루(maltodextrin)를 섭취하였다. 두 집단은 섭취기간 중합숙생활을 하였고, 영양성분이 동일한 식사를 하였으며, 팀 훈련을 통하여 운동량을 동질화시켰다. 섭취 전과후에 신체구성, 유산소성 운동능력, 무산소성 운동능력, 등속성 근기능, 그리고 혈중 젖산농도를 측정한 다음집단 간에, 그리고 검사 간에 비교하여 다음과 같은 결과를 얻었다. 1) b-alanine 집단에서 체지방량과 체지방률이 유의하게 감소되었다. 2) 두 집단 모두에서 VO2max가 유의하게 변화되지 않았다. 3) b-alanine 집단에서 무산소성 운동능력 중 평균파워가 유의하게 증가되었다. 4) 등속성 근기능과 관련하여, b-alanine 집단에서 슬관절 신근의 근지구력이 유의하게 향상되었다. 5) 혈중 젖산농도는 두 집단 모두 유의한 변화가 나타나지 않았지만, 최대운동부하검사 직후와 회복기 중 b-alanine 집단에서 placebo 집단 보다 더 증가되는 경향이 나타났다. 이상의 결과를 종합해 보면, 4주간의 b-alanine 섭취가 중학교 축구선수의 체지방률 감소, 무산소성 운동능력의 향상, 그리고 근지구력의 향상에 도움이 되는 것으로 결론지을 수 있다. It has been known that b-alanine supplementation induce the increment of carnosine in vivo and was effective in delaying fatigue by buffering the hydrogen which was formed during exercise. This study was designed to investigate the effects of 4 weeks of b-alanine supplementation on physical fitness and blood lactate concentration in middle school soccer players. Nineteen middle school soccer players were randomly assigned to either one of two groups, i.e., b-alanine group (n=10) and placebo group (n=9). Subjects in b-alanine group consumed b-alanine 2 g/day during 1st and 2nd week, as well as 3 g/day during 3rd and 4th week, whereas subjects in placebo group consumed maltodextrin in the same manner. All subjects ate same menu and trained same amount at the same training camp during the intervention period. Body composition, aerobic capacity, anaerobic capacity, isokinetic function, and blood lactate concentration during maximal GXT were measured at pre- and post-test. Main results of the present test were as follows: 1) Fat mass and percent body fat decreased significantly in b-alanine group. 2) No significant changes were found in variables related to aerobic capacity in both groups. 3) Average power increased significantly in b-alanine group. 4) Isokinetic muscular endurance increased significantly in b-alanine group. 5) Blood lactate concentration did not change in eithet group; however, blood lactate concentration immediately after maximal GXT in b-alanine group tended to be increased more than placebo group. It was concluded that b-alanine supplementation would have positive effects for improvement of body composition, anaerobic capacity, and muscular endurance in middle school soccer players.